Communication Support for People with ALS. (28th February 2011) - Beukelman, David; Fager, Susan; Nordness, Amy
Abstract : Almost all people with amyotrophic lateral sclerosis (ALS) experience a motor speech disorder, such as dysarthria, as the disease progresses. At some point, 80 to95 % of people with ALS are unable to meet their daily communication needs using natural speech. Unfortunately, once intelligibility begins to decrease, speech performance often deteriorates so rapidly that there is little time to implement an appropriate augmentative and alternative communication (AAC) intervention; therefore, appropriate timing of referral for AAC assessment and intervention continues to be a most important clinical decision-making issue. AAC acceptance and use have increased considerably during the past decade. Many people use AAC until within a few weeks of their deaths.